450. Evaluating First Responders for SARS-CoV-2 Infection in Broward County, Florida. (31st December 2020) - Eckardt, Paula; Goldman, Jennifer M; Claramunt, Jose A Rodriguez; Niu, Jianli; Edwards, Courtney
Abstract: Background: First responders (e.g., emergency medical technicians, firefighters and police) may be at higher risk of SARS-CoV-2 infection and potentially spreading it than the general population due to frequent and close exposure to others. Prevention of first responder infections is important for reducing secondary transmission and maintaining health system capacity. We aimed to evaluate the burden of SARS-CoV-2 infection on first responders, identify risk factors for infection, and to provide health services to help control the current outbreak. Methods: Memorial Healthcare System (MHS), a public healthcare system serving the South Broward Hospital District, together with the National Guard and Florida state governor, opened up a drive-through testing center for SARS-CoV-2 at C.B. Smith Park in Broward County, Florida. All first responders in Broward County, symptomatic or asymptomatic, were being tested. SARS-CoV-2 infection was made as a positive result of real time polymerase chain reaction (PCR) testing on at least one nasal or nasopharyngeal swab. All first responders who test positive for SARS-CoV-2 were informed by test site staff and self-quarantined to limit the spread of the disease. Results: A total of 3, 375 individuals was tested during the period from April 1 to April 29, 2020. The median age was 42 years (IQR 33–52) and 1, 464 (43%) were men. 473 (14%) were symptomatic and 2, 902 (86%) were asymptomatic. 289 (8.5%) of 3, 375 first responders were positive for SARS-CoV-2 infection. These included 54 of 473 symptomatic (11%) and 235 of 2, 902 asymptomatic (8.1%) cases. The rates of SARS-CoV-2 infection were comparable in male vs female (8.1% vs 8.9%, p = 0.429) and in symptomatic vs asymptomatic ( p = 0.173). There is no sex-, age-based differences in susceptibility to SARS-CoV-2 infection among the first responders tested (Figure 1). Laboratory confirmed SARS-CoV-2 among first responders between April 1 and April 30, 2020 in Broward County. Conclusion: First responders carry a significant burden from SARS-CoV-2 infection, with an infection rate of 8.5%, which was comparable in symptomatic and asymptomatic individuals. There is no sex-, age-based differences in susceptibility to SARS-CoV-2 infection in first responders. High priority testing for SARS-CoV-2 must expand to include first responders, particularly asymptomatic individuals. Disclosures: All Authors : No reported disclosures